PENGARUH PEMBERIAN NAPTHALENE ACETIC ACID (NAA) DAN BENZYL ADENINE (BA) TERHADAP KEBERHASILAN SETEK DAN PERTUMBUHAN ANAKAN SANSEVIERIA Sansevieria masoniana ‘Giant’ - Juniarika Silalahi; Tengku Nurhidayah; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sansevieria is potentially as ornamental plants, anti pollutants and medicinal plants which requires development through effort propogation. The aim of the research was to find out the effect of NAA and BA and the combination both of them for the success and bud growth on cutting Sansevieria. The research by giving NAA and BA was conducted at Green House of Agriculture Faculty University of Riau, started from September 2013 to March 2014. This research used completely randomized design (CRD) which consisting of 5 treatments and 3 replications. The treatment were: A = without hormone, B = NAA 1 mg/l, C = BA 1 mg/l, D = NAA    1 mg/l + BA 1 mg/l and D = NAA 0,5 mg/l + BA 0,5 mg/l. Parameters observed were the survival percentage, percentage of root cuttings, number of roots, root length, root volume, percentage of bud growth, number of buds, bud length, number of leaf buds and number of bud roots. Data were analyzed statistically using analysis of variance and further tested by using Duncan’s new multiple range test level 5%. The result showed that the growth of cutting Sansevieria not affected by NAA and BA either as singular or the combination. The growth of cutting Sansevieria affected by physiology and endogen hormone.   Keywords: Sansevieria, cutting, plant growth hormone, growth